Design of Upper limb Rehabilitation Training System for Stroke Patients Based on Goalkeeper Virtual Reality Game - Xingping YANG; Zhuoming CHEN; Zhao GAO (康复学报)
Objective:To develop a virtual reality rehabilitation training system that can be applied to improve the upper limb motor function of stroke patients.Methods:The pathological characteristics of patients with upper extremity dyskinesia were analyzed, and the virtual reality and computer aided games were selected with requirements in upper limb movements. The difficulty levels were determined according to the vectors, based on the motion range of normal upper limbs, and affected by the factors such as reaction speed, muscle strength, balance ability and limb coordination ability. The games were modified to realize the accurate assessment of upper extremity motor dysfunction with the rehabilitation-affecting factors as technical parameters, and gradually rehabilitate the affected limb function with the patient immersed in the scenes of virtual reality games.Results:A rehabilitation training system for improving upper limb motor function of stroke patients by virtual reality technology was developed. Most of the testers were satisfied with the goalkeeper game after trial. After clinical application, it was found that virtual reality rehabilitation training system can significantly improve the upper limb motor function of stroke patients compared with conventional therapy, and the system had good application feedback and strong operability.Conclusion:The upper limb motor training system of virtual reality game can improve the upper limb motor function of stroke patients, and the system has good clinical compliance and operability. Large-scale clinical trials are needed to further verify its efficacy and function.